2009
DOI: 10.1021/bi901403c
|View full text |Cite
|
Sign up to set email alerts
|

The Periplasmic Chaperone Skp Facilitates Targeting, Insertion, and Folding of OmpA into Lipid Membranes with a Negative Membrane Surface Potential

Abstract: The basic biochemical and biophysical principles by which chaperone-bound membrane proteins are targeted to the outer membrane of Gram-negative bacteria for insertion and folding are unknown. Here we compare spontaneous folding of outer membrane protein A (OmpA) of Escherichia coli from its urea-unfolded form and from the complex with its periplasmic chaperone Skp into lipid bilayers. Skp facilitated folding of OmpA into negatively charged membranes containing dioleoylphosphatidylglycerol (DOPG). In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 59 publications
9
66
1
Order By: Relevance
“…Although the presence of PG relieved some of the inhibitory effect of PE lipids on OmpA folding, the PE+PG combination had an additive inhibitory effect on OmpLA folding. Our results therefore disagree with previous suggestions that folding of bacterial OMPs is overall favorable in phospholipids with glycerol head groups (25). Unlike the general trend of PE lipids slowing OMP folding, we demonstrated that PG lipids can either kinetically promote or inhibit folding of individual OMPs in the presence of PE.…”
Section: Significancecontrasting
confidence: 99%
“…Although the presence of PG relieved some of the inhibitory effect of PE lipids on OmpA folding, the PE+PG combination had an additive inhibitory effect on OmpLA folding. Our results therefore disagree with previous suggestions that folding of bacterial OMPs is overall favorable in phospholipids with glycerol head groups (25). Unlike the general trend of PE lipids slowing OMP folding, we demonstrated that PG lipids can either kinetically promote or inhibit folding of individual OMPs in the presence of PE.…”
Section: Significancecontrasting
confidence: 99%
“…Furthermore, because Skp forms a trimer whose binding cavity appears to be too small to accommodate the entire β domain (37), multiple Skp trimers may interact with the ∼30-kDa fragment. Based on recent in vitro experiments, it is possible that the highly basic Skp protein targets the β domain directly to the negatively charged inner leaflet of the OM (38). However, it also is conceivable that other chaperones that have been implicated in OMP biogenesis (SurA and DegP) bind to the EspP β domain but that these interactions are too transient to be detected by our methods.…”
Section: Discussionmentioning
confidence: 98%
“…A second unresolved question is raised by the discrepancy between the requirement for highly fluid membranes for the folding of outer membrane proteins in vitro (56,57) and the presumed low fluidity of the outer membrane (58). Recent observations indicate that at least certain chaperones can help overcome this barrier (59,60). PulS might play such a role.…”
Section: Discussionmentioning
confidence: 99%